Peran Dinas Pendidikan Dan Kebudayaan Kota Malang Dalam Menangani Masifnya Kasus Bullying - Karisma Auliyah Nur Ratu Pertiwi; Ranni Endriana Putri; Rahmah Hidayatus Sholichah (CV. ITTC INDONESIA, 2026)
This research discusses the role of the Malang City Education and Culture Office in handling bullying cases that are rampant in the school environment. Bullying is an act of violence that has a negative impact on students' psychological, social and academic conditions, and is a real threat to human security. This research uses a descriptive qualitative approach with interview, observation, and documentation methods to describe the phenomenon in depth. The results showed that the Education and Culture Office plays an active role as an educational facilitator, driver of school culture change, and shaper of preventive policies. This research also highlights the link between the bullying phenomenon and the achievement of the Sustainable Development Goals (SDGs), especially point 4 on Quality Education.